2015
DOI: 10.1590/abd1806-4841.20153779
|View full text |Cite
|
Sign up to set email alerts
|

Scleredema associated with Sjögren’s syndrome

Abstract: Scleredema adultorum of Buschke is a rare disorder characterized by diffuse swelling and non-pitting induration of the skin usually involving the face, neck, arms and upper trunk. It has been associated with previous infectious diseases, diabetes, paraproteinemia and, more rarely, malignant neoplasms or autoimmune disorders. We report the case of a 30-year-old man who presented with a 2-year history of scleredema. Further investigation led to the diagnosis of primary Sjögren’s syndrome. The association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Although this patient has a mildly elevated hemoglobin A1c level, suggestive of type 3 SAB, the absence of poorly controlled insulin-dependent diabetes suggests that this case is more consistent with the fourth type of SAB, described in association with miscellaneous conditions (ie, HIV, Sjögren syndrome, IgA deficiency, etc) 1, 4. Previous case studies have shown the coexistence of SAB with other rheumatologic diseases, including Sjögren syndrome, rheumatoid arthritis, ankylosing spondylitis, and dermatomyositis 4, 7, 8. To the best of our knowledge, there no report in the literature that describes the simultaneous appearance of SSc and SAB.…”
Section: Discussionsupporting
confidence: 62%
“…Although this patient has a mildly elevated hemoglobin A1c level, suggestive of type 3 SAB, the absence of poorly controlled insulin-dependent diabetes suggests that this case is more consistent with the fourth type of SAB, described in association with miscellaneous conditions (ie, HIV, Sjögren syndrome, IgA deficiency, etc) 1, 4. Previous case studies have shown the coexistence of SAB with other rheumatologic diseases, including Sjögren syndrome, rheumatoid arthritis, ankylosing spondylitis, and dermatomyositis 4, 7, 8. To the best of our knowledge, there no report in the literature that describes the simultaneous appearance of SSc and SAB.…”
Section: Discussionsupporting
confidence: 62%
“…However, comorbidities outside of these three types have also been observed in patients with scleredema; comorbid conditions are summarized in Table 1 [1,[5][6][7][8][9][10]. Some of the conditions include thyroid disease (hyperthyroidism), autoimmune disorders (Sjogren syndrome), and malignancy [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, comorbidities outside of these three types have also been observed in patients with scleredema; comorbid conditions are summarized in Table 1 [1,[5][6][7][8][9][10]. Some of the conditions include thyroid disease (hyperthyroidism), autoimmune disorders (Sjogren syndrome), and malignancy [8,9]. A 30-year-old man with tear production impairment and salivary gland scintigraphy consistent with Sjogren syndrome was also found to have diffuse induration of the skin of the shoulders and upper arms; the diagnosis of scleredema was made by histopathologic examination [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common skin symptoms of Sjögren’s syndrome are dry skin and Raynaud’s phenomenon, which affected 55% and 35% of primary Sjögren’s syndrome patients, respectively [ 7 , 8 ]. However, there are few reports regarding the association of Sjögren’s syndrome with skin cancers, especially the development of multiple skin cancers.…”
Section: Introductionmentioning
confidence: 99%